The crucial role of costing in achieving competitive advantage in business / Musliha Musman and Salwa Muda - Musman, Musliha; Muda, Salwa (Universiti Teknologi MARA, Negeri Sembilan, 2023)
In today's extremely competitive market, it is widely thought that in order to prosper, businesses must build a competitive advantage, which may be accomplished through efficient cost accounting management (Nikkeh et al., 2022; Falahat et al., 2020). Learning cost accounting will help the business understand the costs connected with the items or services that it sells. Cost accounting involves analysing and tracking all costs incurred from the manufacturing process till after-sales service, which management will use to make judgements, and then utilising that knowledge to make decisions. Considering the case of Proton, the company needs to comprehend the costs connected with each product to decide the price at which a vehicle or another item must be marketed. The prices charged do not only cover the direct costs associated with a particular product. There are costs such as manufacturing overhead, which includes machinery costs, occupation charges, and many other costs that must be incurred in order for the product to be ready for sale.